The Effect of Passive-Active Interaction Method on Drag Reduction Performance in Rotating Disk Apparatus - Abdulbari, Hayder A.; Mohamad Amran, Mohd Salleh; Rashed, Musaab K.; M. Halim Shah, Ismail (Informatics Publishing Limited, 2017)
Objectives:Turbulent Drag Reduction (DR) efficacy of diesel fuelin a Rotating Disk Apparatus (RDA) using anionic surfactant of Sodium Lauryl Ether Sulfate (SLES) was investigated with smooth andSV-groove disks(riblets height of 900 and 3100 µm). Methods: The DR efficacy indicates how the torque is being reduced with a tiny amount of additives under a turbulent flow at a Reynolds number (Re) range of 302227 to 453341. The effects of different variables such as rotary disk type (smooth or structured), surfactant concentration, and Reynolds number were also studied. Findings: SLES shows a good ability to reduce the frictional drag forces with smooth and SV-groove of height 3100µm. In contract, there is no drag reduction can be observed by using this surfactant with SV-groove of height 900 µm. Application/Improvements: The passive-active interaction method can be used to improve petroleum liquid flow in pipelines.